Invasive pit pattern, macronodule and depression are predictive factors of submucosal invasion in colorectal laterally spreading tumours from a Western population. Issue 10 (1st December 2018) - Soliman, Heithem; Brieau, Bertrand; Guillaumot, Marie-Anne; Leblanc, Sarah; Barret, Maximilien; Camus, Marine; Dior, Marie; Terris, Benoit; Coriat, Romain; Prat, Frédéric; Chaussade, Stanislas
Abstract : Background: Laterally spreading tumours are separated in subclasses: granular, homogenous or nodular mixed; and non‐granular, flat or pseudodepressed. For every subtype, a proper risk of submucosal invasive cancer has been described in Asian series. Objective: The aim of the study was to determine the rate of cancer and submucosal invasive cancer in a Western series of endoscopic‐resected laterally spreading tumours and their endoscopic predictive factors. Methods: A total of 374 laterally spreading tumours ≥20 mm were resected by endoscopy in our single centre between 2012–2016. We analysed endoscopic and pathological data from our prospective database, determining the rates of cancer and submucosal invasive cancer according to the subtype of laterally spreading tumour. Results: The rates of submucosal invasive cancer for granular homogenous, granular nodular mixed, non‐granular flat, non‐granular pseudodepressed laterally spreading tumours were 4.9%, 15.9%, 3.0% and 19.4%, respectively. Endoscopic mucosal resection was used in 58.0% and endoscopic submucosal dissection in 42.0%. Endoscopic submucosal dissection was associated with a higher rate of en‐bloc resection (87.3% vs 26.3%; p  < 0.0001), and a lower risk of recurrence (7.6% vs 15.2%; p  = 0.026). Adverse event rates were not statistically different (9.5% vs 6.4%, p  = 0.26). Predictive endoscopic factors of submucosal invasive cancer were: invasive pit pattern (hazard ratio = 33 (8.81–143.3)), non‐granular pseudodepressed laterally spreading tumours (hazard ratio = 11.9 (0.89–146.2)), and granular nodular mixed laterally spreading tumours (hazard ratio = 3.42 (0.99–13.0)). Conclusions: The risk of submucosal invasive cancer varies according to the laterally spreading tumour subtype. Three factors were associated with submucosal invasion and should justify an endoscopic submucosal dissection: non‐granular pseudodepressed laterally spreading tumours, granular nodular mixed laterally spreading tumours subtypes and invasive pit pattern.